Patient Satisfaction with Nursing Services in Public and Private Hospitals in Ahwaz, Iran - Pourmoosavi, Hossein; Torabipour, Amin; Alvani, Jamalledin (International Journal of Engineering and Technology, 2018)
Introduction: Patient satisfaction is a complex phenomenon that influenced by various factors. Nursing services are one of the most important aspects affecting patient satisfaction. The aim of this study was to compare patient satisfaction with nursing services in public and private hospitalsMethod: This is a cross-sectional study. The statistical population consisted of patients referring to public and private hospitals in Ahvaz in 2017. According to sample size formula, 560 patients were selected as a samples in public (N=350) and private (N=210) hospitals. To assess patient satisfaction, a valid questionnaire including 24 items in five dimensions including nursing behaviors, nursing care, patientsâ€™ education, speed of nursing practice, and trust were used. Data were analyzed using SPSS.22 software and t-test, ANOVA, and Pearson correlation coefficient.Results: the mean score of patient satisfaction with nursing care in public hospitals was (13.4, 95% CI 13.2â€‰to13.8) and more than private hospitals (11.6, 95% CI 11.1to12.1). In public hospitals, patient education dimension was the highest score (3.1, 95% CI 2.9to3.2). In private hospitals, nurses manner and behavior most scored (2.6, 95% 2.5to2.7).Conclusion: The present study showed that in public hospital patientsâ€™ satisfaction with nursing services was moderate and in private hospital was poor..Â Â